2003
DOI: 10.1309/dcxa-xfvc-chvh-yu41
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and Error Rates Using Blinded Review to Evaluate Surgical Pathology of Biopsy Material

Abstract: Blinded review has been shown to be an excellent method to detect disagreements and errors and improve performance in gynecologic cytology. Preliminary studies suggest it may be valuable in surgical pathology. We reviewed 5,000 sequential outpatient surgical pathology biopsy cases without knowledge of the original diagnosis or history and compared the results with those of the original diagnosis. Complete agreement was obtained in 91.12% of cases. The technique of blinded review of surgical pathology biopsy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Threshold effects have been recognized as an important source of variation in other studies. 22 Such variation might be minimized by more uniform application of diagnostic criteria.…”
Section: Threshold Effectsmentioning
confidence: 99%
“…Threshold effects have been recognized as an important source of variation in other studies. 22 Such variation might be minimized by more uniform application of diagnostic criteria.…”
Section: Threshold Effectsmentioning
confidence: 99%
“…[3][4][5][6][7] Studies using interlaboratory review of pathology material have shown that the rate of disagreement depends on the type of consultation (pathologist directed vs patient/clinician directed 8 ), the source or tissue type of material, 4,[9][10][11] the type of diagnosis, 11 the number of slides examined, 11 the use of immunohistochemistry, 11 and whether the report has more than 1 pathologist's name on it. 11 We recently noted that the rate of disagreement in both our incoming and outgoing patient/clinician-directed interlaboratory anatomic pathology consults had declined over time.…”
Section: Conclusion: Disagreements In Interlaboratory Anatomic Pathomentioning
confidence: 99%
“…Within a juridical context, knowledge of the outcome may likewise influence the reviewing pathologist. In this situation in particular, a blinded review is a prerequisite for an impartial evaluation—a problem well known in both pathology and radiology 52 53. On re-examination of missed morphologically determined diagnoses, the type of review can influence the outcome 54–56.…”
Section: The Aetiology Of Errormentioning
confidence: 99%